Association between adolescent pregnancy and infant mortality: a population-based study - Rahman, Farhana; Rashid, Mamunur; Khan Chowdhury, Mohammad Rocky; Kader, Manzur (Frontiers in Pediatrics, 2025)
BackgroundBangladesh continues to grapple with a persistently high infant mortality rate, currently at 38 deaths per 1,000 live births. Adolescent pregnancy poses significant health risks for both mothers and infants globally, yet its specific impact on infant mortality in Bangladesh remains underexplored. Therefore, this study aims to investigate the association between adolescent pregnancy and infant mortality in Bangladesh.MethodsThis cross-sectional study analyzed data from the Bangladesh Demographic and Health Survey 2017–18, focusing on 8,759 infants born to women aged 15–49 years. Adolescent pregnancies were categorized into four groups: <16 years, 16–17 years, 18–19 years, and >19 years. Potential covariates included sociodemographic factors (mothers' age, fathers' occupation, religion), contextual factors (place of delivery, access to media and technology), and healthcare utilization (antenatal and postnatal care). Bivariate logistic regression assessed associations between adolescent pregnancy and infant mortality, presenting adjusted odds ratios (AOR) with 95% confidence intervals (CI) while controlling for these covariates.ResultsThe mean age of mothers at first birth was 18.53 years. Among the 8,759 infants studied, 328 (3.74%) died before reaching 12 months of age. Infants born to mothers younger than 16 years initially showed higher odds of mortality (AOR: 1.45, 95% CI: 1.05–2.01); this association persisted even after adjusting for sociodemographic and contextual factors (AOR: 1.41, 95% CI: 1.01–1.96). However, after controlling for healthcare utilization, the relationship was no longer statistically significant (AOR: 1.06, 95% CI: 0.56–1.99).ConclusionsDelaying childbirth from adolescence to adulthood may reduce infant mortality in Bangladesh. However, adolescent pregnancy alone does not increase infant mortality risk after accounting for healthcare utilization, such as antenatal and postnatal care. Improving access to quality healthcare is crucial for lowering infant mortality. Future cohort studies are needed to better understand the relationship between maternal age and infant health outcomes.